HIGHER EDUCATION INTERNATIONALIZATION: FACTORS RESEARCH SHAPING THE CHOICE OF HIGHER EDUCATION INSTITUTION FOR FOREIGN STUDENTS - Bibhuti B Pradhan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Internationalization is now one of university's key goals not only in Europe but worldwide as well. Most Higher Education Institutions (HEIs) provide internationalization as one of their strategies, thereby contributing to the creation of English-language study programs, involvement of guest lecturers, and participation in other activities designed to attract foreign staff and students. Foreign students are an asset to the HEIs they research there. The study aims at identifying and assessing factors affecting the choice of a higher education institution (HEI) for foreign students in order to recommend more changes for higher education internationalization. Companies expect students with a certain range of skills, experience and ability to execute work tasks effectively. Families, as the study experience's key backers, foresee some improvements in student personalities, as well as a learned desire to find a successful job or set up their own company after graduation. However, this paper focuses on the most critical of these categories of clients – a student who is mainly responsible for selecting a higher education institution where he / she receives his / her study experience.